Legal Protection of The Parties to The Implementation of The Sale and Purchase Agreement through E-Commerce - Via Puja Laksana; Moh. Indra Bangsawan (Proceeding International Conference Restructuring and Transforming Law, 2025)
This research explores the dynamics of e-commerce in the context of the balance of rights and obligations between business actors and consumers, with a focus on the implementation of a regulatory framework that ensures the security and convenience of digital transactions. The research methodology adopts a normative juridical approach with descriptive characteristics, using data collection techniques through literature study and qualitative descriptive analysis to obtain a comprehensive understanding of the phenomenon under study. Research results indicate the existence of specific objects in e-commerce contracts that are explicitly regulated in Article 1320 3rd of the Civil Code jo Article 9 of Law No. 1 of 2024 concerning the Second Amendment to Law No. 11 of 2008 concerning Electronic Information and Transactions. Legal protection for consumers in transactions through e-commerce platforms such as Shopee is implemented through regulatory triangulation which includes the Civil Code, Consumer Protection Law No. 8 of 1999, and the Electronic Information and Transactions Law. The regulatory framework covers aspects of consumer rights protection and loss compensation mechanisms. E-commerce platforms implement liability systems through comprehensive terms of service, including reporting and consumer loss resolution procedures. This research underscores the significance of holistic legal protection in creating an accountable and transparent e-commerce ecosystem, with practical implications for the development of more adaptive digital commerce regulations.